No relation between body mass and gastro-oesophageal reflux symptoms in a Swedish population based study. Issue 1 (1st July 2000) - Lagergren, J; Bergström, R; Nyrén, O
Abstract : BACKGROUND: There is a widespread notion that obesity leads to gastro-oesophageal reflux but scientific evidence of an association is limited and inconsistent. AIMS: To estimate the strength of the association between body mass and reflux symptoms, we performed a population based cross sectional interview study. SUBJECTS: Population based, randomly selected, middle aged or elderly persons in Sweden in 1995–1997. METHODS: At face-to-face interviews we asked a stratified sample of Swedes about body measures and occurrence of reflux symptoms. Odds ratios (OR) with 95% confidence intervals (CI), calculated by logistic regression with multivariate adjustments for covariates, were the measures of association. RESULTS: Reflux symptoms occurring at least once a week more than five years before the interview were reported by 135 (16%) of the 820 interviewees. Among those who had ever been overweight during adulthood (body mass index (BMI) ⩾25 kg/m 2 ), the OR of having recurrent reflux symptoms was 0.99 (95% CI 0.66–1.47) compared with those who were never overweight. There was no association between BMI at age 20, BMI 20 years before the interview, or maximum adult BMI and occurrence of reflux symptoms: ORs per unit increase in BMI were 1.00 (95% CI 0.93–1.09), 1.03 (95% CI 0.96–1.10), and 1.01 (95% CI=0.95 1.07), respectively. There was no association between BMI and severity or duration of reflux symptoms. CONCLUSIONS: Gastro-oesophageal reflux symptoms occur independently of body mass index. Weight reduction may not be justifiable as an antireflux therapy.